A zinc finger protein gene TksC3H20 positively regulates salt tolerance in Taraxacum kok-saghyz under salinity - Ran Wan; Boxuan Yuan; Fengyan Fang; Wenhao Wu; Shuangxian Liu; Yuxin Li; Xiaoyou Wu; Wei Li; Shugang Hui; Xuchu Wang (Plant Science, 2026)

Coordination-tailored high-spin Fe-MOF membrane electrode ensures selective singlet oxygen electrosynthesis: Non-radical emerging contaminants removal - Jian Sun; Shaofeng Li; Lijun Zhu; Boyang Meng; Boxuan Yang; Huan Wang; Tongzhou Liu (Water Research, 2026)

Prediction of breakthrough time in hydrogen purification from coke oven gas using deep learning model - Yuqi Zhang; Boxuan Zhang; Zhibin Liu; Leiming Xiong; Yanchuan Cheng; Minke Huang; Cheng Lu; Hengcong Tao; Jingfa Li; Ziming Hu; Bohong Wang; Yue Su (Journal of Cleaner Production, 2026)

Long-term organic amendments regulate cbbL-harboring bacterial community via soil physicochemical properties and enzyme activities in a paddy soil - Jiangbing Xu; Boxuan Li; Yuhao Wu; Lei Liu; Guoyi Zhou; Xiaoli Liu; Ling Chen; Meng Wu; Xiaoyan Ma; Catherine Preece; Daming Li; Ming Liu (Journal of Soils and Sediments, 2026)

Construction of recombinant OPIV3 virus vectoring bivalent Mycoplasma ovipneumoniae adhesins - Xu Zhang; Yijia Liu; Boxuan Yin; Changyan Li; Miao sun; Qinghong Xue; Jinhai Huang (Archives of Virology, 2026)

Zero-solvent-emission rapid synthesis of aerogel beads: A food-colorant adsorbent with biocompatibility and facile separation - Boxuan Peng; Jiahui Li; Tong Wu; Shiyi Wang; Fangzheng Zhao; Chunyue Zhao; Qingyun Liu; Enchang Liu; Huizhen Han; Siyuan Yu; Jinfeng Xing (Chemical Engineering Journal, 2026)

Unpaved road-altered confluence networks exacerbate soil organic carbon loss in mountainous forested catchments - Zaihui Yu; Qinghe Zhao; Shengyan Ding; Jinhai Yu; Boxuan Liu; Wanfu Feng; Yuefeng Li; Jiliang Zhou (Journal of Hydrology, 2026)

Dual-crosslinked injectable polysaccharide-based hydrogel with synergistic photothermal-controlled release of black phosphorus-baicalein for accelerating wound healing - Huizhen Han; Zhen Wang; Tong Wu; Fangzheng Zhao; Shuaibing Huang; Boxuan Peng; Chunyue Zhao; Qiqi Han; Enchang Liu; Qingyun Liu; Jinfeng Xing (Carbohydrate Polymers, 2026)

Deep learning-based morphological analysis of human sperm - Yiran Xu; Yuqiu Chen; Boxuan Zhang; Yimo Yan; Hongen Liao; Ran Liu (Medical & Biological Engineering & Computing, 2026)

Soil moisture variability of typical mixed forests in the north-south climatic transitional zone of China - Yu Mei; Qinghe Zhao; Peikun Li; Xiaojian Qin; Boxuan Liu; Zhize Li; Tingting Wang; Shengyan Ding (Journal of Environmental Management, 2025)

Enhanced Li storage performance of high-entropy spinels by electronic structure and crystallinity dual optimization - Naixuan Ci; Yuelin Wang; Yixuan Hu; Linshan Zhu; Yinghe Zhang; Boxuan Cao; Xi Lin; Lijie Ci; Guoqiang Xie; Xingjun Liu; Kolan Madhav Reddy; Hua-Jun Qiu (Chemical Engineering Journal, 2025)

Cationic liposome-mediated scavenging of cell-free DNA: An innovative and alternative therapeutic approach for efficient treatment of dry eye disease - Juan Wang; Jialuo Zhang; Shujing Liu; Jing Tang; Jiajun Liu; Ying Huang; Huazhang Zeng; Hu Yang; Boxuan Li (Chemical Engineering Journal, 2025)

Monofactorial control of carbon dot emission in solvent-free synthesis for wide-gamut light emitting diodes - Xin Wang; Boxuan Yao; Wenjing Song; Junnan Zhang; Mingyang Zhou; Wei Hu; Lei Zhao; Jian Liu; Shenghong Yang (Chemical Engineering Journal, 2025)

A starch-like polysaccharide isolated from Hirsutella sinensis mycelia alleviates DSS-induced colitis in mice by strengthening the intestinal barrier, maintaining immune homeostasis, and modulating the gut microbiota and SCFA metabolism - Yu Li; Hailiang Wang; Hongtao Bi; Jingyue Feng; Tingting Gao; Dai Dong; Guoqiang Li; Boxuan Liu; Hongyan Yuan; Weihua Ni (Food Bioscience, 2025)

Emission characteristics, environmental impacts and health risk assessment of volatile organic compounds from the typical chemical industry in China - Kaitao Chen; Xin Gu; Min Cai; Weicheng Zhao; Boxuan Wang; Haoran Yang; Xingang Liu; Xingru Li (Journal of Environmental Sciences, 2025)

Thiophene and acetylene functionalized conjugated organic polymers with hollow nanotube structure toward high-performance photocatalytic H2O2 production - Yuntong Li; Boxuan Ding; Yan Sui; Wentong Chen; Dongsheng Liu; Wei Huang; Xiaodan Li; Wei Wang; Hong Zhong; Cheng Liu (Journal of Environmental Chemical Engineering, 2025)

Single-cell integrated transcriptomics reveals the role of keratinocytes in head and neck squamous cell carcinoma - Shaokun Liu; Meng Lian; Boxuan Han; Jugao Fang; Zhenlin Wang (Journal of Applied Genetics, 2024)

Triple-crosslinked double-network alginate/dextran/dendrimer hydrogel with tunable mechanical and adhesive properties: A potential candidate for sutureless keratoplasty - Wen Zhang; Shujing Liu; Lixiang Wang; Boxuan Li; Mengzhen Xie; Yingping Deng; Jialuo Zhang; Huazhang Zeng; Li Qiu; Lisha Huang; Tao Gou; Xiaobo Cen; et al. (Carbohydrate Polymers, 2024)

Simultaneous nitrification and denitrification in a hybrid activated sludge-membrane aerated biofilm reactor (H-MABR) for nitrogen removal from low COD/N interflow: A pilot-scale study - Hengyi Liu; Lei Li; Wenjie Ye; Boxuan Zhao; Yun Peng; Guotao Liu; Xiaofeng Gao; Xuya Peng (Journal of Environmental Management, 2024)

Impacts and influencing pathways of urbanization on carbon–water-energy-food nexus across Chinese cities - Chenggang Li; Yong Liu; Zhenci Xu; Gang Zhao; Youhui Bao; Chengcheng Cai; Yu Lu; Yufeng Mao; Alexander Boxuan Wang; Liang Wu (Environment, Development and Sustainability, 2024)
Food, water, energy and carbon (F-W-E-C), as important factors of urban development, have synergistic effects and trade-off effects with each other. Scientifically assessing the impact of urbanization on the F-W-E-C nexus is beneficial to optimize the urban development layout and achieve the sustainable urban development. Nevertheless, extant studies have not evaluated the impact and influencing pathways of urbanization on the F-W-E-C nexus. In this study, the Coupling Coordination Degree Model is used to explore the F-W-E-C nexus of 252 prefecture-level cities in China. The panel data model and mediating effect model are utilized to study the impact of urbanization on the F-W-E-C nexus and the impact pathways. This study finds that the F-W-E-C nexus across Chinese cities is weak trade-off. The urbanization promotes the synergy of F-W-E-C. The positive impact is greater in the central cities than in the eastern and western cities, and is greater in medium-sized cities than in small cities, large cities and above. The technological progress is an important pathway of urbanization impacting the F-W-E-C nexus, and assists urbanization to generate a positive influence on the F-W-E-C nexus. This research has implications for promoting a systematic, orderly, and rational coordination development of F-W-E-C and for sustainable urbanization development in China and the world.

CD8 + T cell response in QuantiFERON-TB Gold Plus testing was associated with tuberculosis recurrence: a 2-year prospective study - Henan Xin; Xuefang Cao; Boxuan Feng; YiJun He; Tonglei Guo; Jiang Du; Lingyu Shen; Yuanzhi Di; Zisen Liu; Dakuan Wang; Bin Zhang; Zhanjiang Zhang; et al. (Infectious Diseases, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Seasonal variations of microplastics in surface water and sediment in an inland river drinking water source in southern China - Wenyu Zhao; Jing Li; Mengyue Liu; Rui Wang; Boxuan Zhang; Xiang-Zhou Meng; Shengwei Zhang (Science of The Total Environment, 2024)

Emerging and legacy perfluoroalkyl and polyfluoroalkyl substances (PFAS) in surface water around three international airports in China - Jing Liu; Zhen Zhao; Jie Li; Xia Hua; Boxuan Zhang; Caijun Tang; Xinyi An; Tian Lin (Chemosphere, 2023)

Understanding the reversal dilution effect of the species sampling in the negative temperature coefficient region - Yingtao Wu; Zhaoming Mai; Boxuan Rao; Jie Liu; Chenglong Tang; Zuohua Huang (Fuel, 2023)

Solvothermally silver doping boosting the thermoelectric performance of polycrystalline Bi2Te3 - Wen-Yi Chen; Xiao-Lei Shi; Qishuo Yang; Meng Li; Wanyu Lyu; Ting Liu; Tianyi Cao; Boxuan Hu; Weidi Liu; Shuai Sun; Yuanqing Mao; Matthew Dargusch; et al. (Chemical Engineering Journal, 2023)

Secondary metal doped cuprous-cyanoimidazole frameworks for triple-mode detection of dopamine - Hua Wei; Jian Liu; Xin Wang; Zihan Li; Lijuan Ju; Boxuan Yao; Jiarui Zhou; Lei Zhao; Mingyang Zhou; Jie Zhang; Shenghong Yang (Analytica Chimica Acta, 2023)

Design and Field Test of a Remotely Controlled Self-propelled Potato Harvester with Manual Sorting Platform - Boxuan Jia; Wei Sun; Zhiwei Zhao; Hucun Wang; Hua Zhang; Xiaolong Liu; Hui Li (American Journal of Potato Research, 2023)

Bridging environmental and biological monitoring: Constructing platform for hexavalent chromium detection and cancer-cells screening based on red fluorescent carbonized polymer dots - Xin Wang; Jinshuang Hu; Boxuan Yao; Hua Wei; Caiyun Zhang; Jiarui Zhou; Jian Liu; Shenghong Yang (Chemical Engineering Journal, 2023)

Down-regulation of miRNA-451a and miRNA-486-5p involved in benzene-induced inhibition on erythroid cell differentiation in vitro and in vivo - Boxuan Liang; Yuncong Chen; Weixin Yuan; Fei Qin; Qian Zhang; Na Deng; Xuexing Liu; Xiaoju Ma; Xue Zhang; Bo Zhang; Qifei Deng; Ming Huang; et al. (Archives of Toxicology, 2018)